Supplementary Materials: Status of Hypertension and its Determinants among Teachers in Tribhuvan University Campus, Kirtipur, Kathmandu - Khadka, Krishna; Uprety, Pravat (Nepalese Journal of Statistics, 2023)
As mentioned in the manuscript.